Non-genetic factors affecting early growth traits and survival in Horro sheep - Abegaz, Solomon; Duguma, G.; Gelmesa, U.; Terefe, F.; Negussie, E.; Rege, J.E.O. (2002)
Factors affecting the early growth and survival of indigenous Ethiopian Horro sheep were identified and the influence of each was assessed, based on data collected from 1978 97 from 4031 lambs at Bako Research Centre, Ethiopia. Year of birth, sex, type of birth or rearing, and parity had significant (P < 0.01) effects on birth weight (BWT), weaning weight (WWT), and six month weight (6MWT). With the exception of parity, the same factors affected yearling weight (YWT). Male lambs were heavier by 0.14, 1.1, 1.9, and 4.2 kg than females in BWT, WWT, 6MWT, and YWT. Single born lambs were heavier by about 0.5 kg than multiple born lambs at birth. Lambs born from primiparous ewes were lighter by 0.2 0.3 kg than lambs born from multiparous ewes at birth. With the exception of effect of type of birth and ewe age on survival to 3 and 7 days of age, respectively, year of birth, ewe (dam) age, type of birth, and BWT had significant (P < 0.01) effect on survival from three days to one year of age. The survival of multiple-born lambs was 0.8, 3.7, 8.3, 12.2, and 12.496 lower than single-born lambs at the age of 3, 30, 90, 180, and 365 days, respectively. Lambs born from primiparous ewes had lower survival rates compared to those born from multiparous ewes. Survival was very low in lambs with low BWT and improved with increase in BWT. In general, there are indications that there exists a critical BWT (about 2.6 kg) below which the survival of lambs declines drastically.